Effectiveness of Special Autonomy Policy Implementation in Effort to Increase School Participation in Fakfak Regency West Papua - Nof, Faisal; Wijaya, Andy Fefta (JPAP: Jurnal Penelitian Administrasi Publik, 2019)
One of the objectives of implementing Papua's special autonomy is to improve the quality of human resources by improving the access of Papuan children's education. The education index can provide a picture of the welfare of society from the human dimension. Special Autonomy fund available is not a modest amount, therefore it should be adequate to assist in improving the quality and quantity of human resources in the education sector. It is conducted by building facilities and infrastructures to support education. The implementation of special autonomy in the Fakfak Regency West Papua has lasted for approximately one and a half decades. Therefore, it is necessary to examine how the effectiveness of special autonomy policy implementation in this province. It is conducted especially in order to increase public access to education. The amount of the Special Autonomy Fund should be able to accelerate the development process. The Community hopes that the Regent of Fakfak would fulfill their promise made during the election campaign. The Regent is expected to conduct mission and vision focusing in improving education in Fakfak Regency, up to villages and cities inland. The education development mapping should be improved because education is the spearhead of all aspects of development. Keywords: effectiveness of special autonomy, special autonomy of Papua, special autonomy education policy.